Cutaneous protothecosis reminiscent of unilateral solar elastotic bands of forearm in an immunocompromised patient - Yi-Hsin Ho; Yun-Wen Chiu; Chen-Yi Wu; Han-Nan Liu (Wolters Kluwer Medknow Publications, 2018)
We report a case of cutaneous protothecosis due to Prototheca wickerhamii in an elderly male with hepatocellular carcinoma (HCC), decompensated liver cirrhosis, diabetes mellitus, hypertension and coronary artery disease, who presented with a large dull erythematous plaque over right upper limb stretching from the lower third of the distal upper arm to near the wrist. A biopsy revealed marked, band-like solar elastosis in the upper dermis, a pathologic pattern that resembles solar elastotic bands of forearm. However, the following Periodic acid-Schiff stain and fungal culture confirmed the diagnosis of protothecosis. Our finding added a new pattern to the list of the highly variable cutaneous manifestations of protothecosis. Keywords: Immunocompromise, Protothecosis, Prototheca wickerhamii, Solar elastotic bands of forearm